HUBUNGAN ANTARA LOYALITAS PELANGGAN DENGAN LINGKUNGAN BELANJA DALAM MENCIPTAKAN PROFITABILITAS JANGKA PANJANG - Andriyani, Lilik (Universitas Muhammadiyah Magelang, 2006)
The rapidly and constantly changing business has forced business ro reconsider their strategies in maintaning ther customer base. This article presents the effect of customer loyalty on shopping environment and shopping environment and shopping behavior to reach the long-term profotability. The relationship between customer loyalty and satisfaction, profit ability is described in the framework of relationship marketing. The importance of loyal customer and their impact on business profitability is undisputed. Various strategy to keep their customer base incluidinf on integrated approach of maintaining and managing customers relationship must be taken. However, in order to succeed. The company have to develop loyalty programs to customers who have a high satisfation, high loyalty and customer who will stay and be supportiv of company to provide long-term beneficial relationship which eventually will icrease profitability. The role of cunsomer self-regulation also can be viewed as moderator of relationship shopping emotion and arousal of cunsomer. Cunsomer shopping behavior dimension taht emerge from shopping environment can explained using M.R environment psychology and it has applied to the study of store atmosphere.